2001
DOI: 10.1016/s0014-5793(01)02993-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rabaptin‐5, rabex‐5, and GM130 as putative effectors of rab33b, a regulator of retrograde traffic between the Golgi apparatus and ER

Abstract: The role of rab33b, a Golgi-specific rab protein, was investigated. Microinjection of rab33b mutants stabilised in the GTP-specific state resulted in a marked inhibition of anterograde transport within the Golgi and in the recycling of glycosyltransferases from the Golgi to the ER, respectively. A GSTrab33b fusion protein stabilised in its GTP form was found to interact by Western blotting or mass spectroscopy with Golgi protein GM130 and rabaptin-5 and rabex-5, two rab effector molecules thought to function e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 49 publications
9
90
0
Order By: Relevance
“…This raises the possibility that the Rab5 GEFs Rabex-5 and Rin1 may also function as Rab11B GEFs, hence coupling the Rab5-and Rab11-regulated endocytic recycling activities (Bucci et al, 1994;Schlierf et al, 2000), as has been observed for yeast GEFs linking exocytic Rabs (Wang and Ferro-Novick, 2002). Similarly, the expression profile of Rabaptin-5 (Ohya et al, 1998) showed a stronger correlation with Rab33B than with Rab5 isoforms (Figure 2), consistent with the recent biochemical evidence that Rabaptin-5 also interacts with Rab33B (Valsdottir et al, 2001). We also noted that TRAPPC4, a mammalian homologue to a component of the Ypt1/Rab1 specific yeast GEF Trapp complex (Jones et al, 2000), clustered with Rab1B/C, suggestive of an evolutionary conserved function in the Rab1 hub in early exocytic pathways of mammalian cells.…”
Section: Rab Regulators Rab Gtpases Do Not Function In Isolationsupporting
confidence: 88%
“…This raises the possibility that the Rab5 GEFs Rabex-5 and Rin1 may also function as Rab11B GEFs, hence coupling the Rab5-and Rab11-regulated endocytic recycling activities (Bucci et al, 1994;Schlierf et al, 2000), as has been observed for yeast GEFs linking exocytic Rabs (Wang and Ferro-Novick, 2002). Similarly, the expression profile of Rabaptin-5 (Ohya et al, 1998) showed a stronger correlation with Rab33B than with Rab5 isoforms (Figure 2), consistent with the recent biochemical evidence that Rabaptin-5 also interacts with Rab33B (Valsdottir et al, 2001). We also noted that TRAPPC4, a mammalian homologue to a component of the Ypt1/Rab1 specific yeast GEF Trapp complex (Jones et al, 2000), clustered with Rab1B/C, suggestive of an evolutionary conserved function in the Rab1 hub in early exocytic pathways of mammalian cells.…”
Section: Rab Regulators Rab Gtpases Do Not Function In Isolationsupporting
confidence: 88%
“…Thus, the observed effects of RUTBC1 knockdown on tyrosinase/Tyrp1/Dct signals are most likely attributable to excess activation of Rab32/38, rather than of Rab33B. However, because Rab33B has been shown to be involved in the autophagosome maturation step (22,38) and the retrograde Golgi transport pathway (39), and because decreased tyrosinase signals were observed in Rab33B(Q92L)-expressing cells, Rab33B may participate in melanogenic enzyme trafficking in melanocytes in a different way from Rab32/38, i.e. by regulating autophagy or retrograde Golgi transport.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Rab5 effector EEA1 has been shown to bind syntaxin 6, a SNARE implicated in trafficking between the trans-Golgi network and early endosomes (45). In addition to binding Rab5, rabex-5 and rabaptin-5 directly interact with Rab33b, a GTPase implicated in retrograde transport from the Golgi to the endoplasmic reticulum (46,47). Recently, rabaptin-5 was reported to form a complex with rabphilin-3, a protein implicated in the control of exocytosis and endocytosis in the nerve terminal (48 -51).…”
Section: Discussionmentioning
confidence: 99%